Studi Analisis Kinerja Pegawai Kantor Camat Malinau Selatan - Rahmawati Rahmawati; Milwan Milwan; Soesilo Wibowo (Mahesa Research Center, 2022)
This article aims to discuss employee performance issues within the South Malinau District Office. The problem is focusing on the achievement of employee performance according to indicators of individual ability, motivation, support received, the existence of the work they do and their relationship with the organization, and the factors that influence it. Research approach using Organizational performance theory references from Robbins and Judge and Kadarisman. The data were collected through observation and interviews and analyzed qualitatively. This study concludes that the performance of employees at the Malinau Selatan Sub-district Office shows low performance based on employee performance indicators and influence by factors both from internal and external employees.